Design and study of psychometric properties of the Community Attitude to Abortion Scale (CAAS) with the Chilean population: Autonomy and Stigma - Pérez Sánchez, Beatriz; Burgos Padilla, Juan José; Alveal-Álamos, Carolina; Concha-Salgado, Andrés; Jara Sepúlveda, Luisa; Rodríguez Díaz, Francisco Javier (Frontiers in Psychology, 2022)
Introduction Attitudes toward abortion are related to structural, cultural, and direct gender-based violence. This violence can affect women’s mental, physical and reproductive health. Therefore, it is essential to know the nature of community attitudes toward abortion. Since we currently do not have an instrument that measures attitudes towards abortion in Chile, we set the objective of this study to design the Community Attitude to Abortion Scale (CAAS) and analyze its psychometric properties in a Chilean community population. Methods This work is an instrumental design study. Using a sampling of panelists by sociodemographic quotas, we obtained a sample of 1,223 participants with a mean age of 36.7 years (SD = 13.56). Results As a result, we obtained a scale of 18 items and two correlated factors, Autonomy and Stigma. This structure fits better as an Exploratory Structural Equations Model (ESEM). Both factors have excellent internal consistency. In addition, we obtained evidence of concurrent and discriminant validity: The scores on the factors of the Universal Religious Involvement Scale (I-E12) correlated negatively with Autonomy and positively with Stigma; participants with low levels of identification with a right-wing political orientation, with high levels of identification with a leftwing, pro-feminist, pro-LGBTQ +, and pro-euthanasia political orientation, obtained higher mean scores on Autonomy and lower on Stigma. Discussion The CAAS is an adequate tool for use with the Chilean community population, with evidence of consistency and validity. La CAAS is the first tool to measure attitudes to abortion in this country.